Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Jasa Percetakan Pada CV Rahuma Cahaya Jaya Digital Printing di Puri Beta Kota Tangerang - Alfath, Zakiah Shafna; Kumara, Dedek (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of product quality and service quality on the decision to purchase printing services at CV Rahuma Cahaya Jaya Digital Printing in Puribeta, Tangerang City. The study uses a quantitative approach with a sample of 97 respondents. Data analysis was conducted through instrument testing, classical assumption testing, simple and multiple linear regression analysis, correlation coefficient testing, t-testing, F-testing, and coefficient of determination testing. The results of the study indicate that product quality and service quality each have a positive and significant effect on purchasing decisions. Simultaneously, both variables also have a significant effect on purchasing decisions. The regression model obtained is Y = 19.112 – 0.025 X1 + 0.904 X2 with a coefficient of determination value of 63.7%, which shows that most of the variation in purchasing decisions can be explained by product quality and service quality, while the rest is influenced by other factors outside the scope of this study. These findings confirm that improving product quality and service quality are important strategies in increasing consumer purchasing decisions in printing services.